Pengaruh aplikasi edible coating gel lidah buaya (Aloe Vera L.) dengan penambahan carboxymethyl cellulose terhadap mutu buah melon (Cucumis Melo L.) potong - Rohula Utami; Alifa Sekar Jannah; Asri Nursiwi (AGROINTEK, 2025)
Fresh-cut fruit consumption has been increasing due to its health benefits, such as fresh-cut melons. Fresh-cut melons have a very short shelf-life due to minimum processing (peeling, cutting), which results in high levels of spoilage and contamination caused by microorganisms that can rapidly degrade fruit quality and increase the risk of food contamination, which can cause consumer health problems. Edible coating is one of the methods used to prevent the damage caused by minimally processed fruits. Aloe vera is an alternative edible coating material that contains polysaccharides and antimicrobial agents to inhibit fruit quality degradation. However, aloe vera edible coating is weak in its gel consistency, so a stabilizer needs to be added, one of which is carboxymethylcellulose (CMC). This research was aimed to determine the effect of aloe vera gel edible coating application with the addition of various concentrations of carboxymethylcellulose on the physical, chemical, and microbiological properties of fresh-cut melon stored for two days at room temperature (27-30oC) and six days at refrigerated temperature (5oC). The concentration of CMC varied at 0.5%, 1%, and 1.5%. The results showed a significant effect of adding various concentrations of CMC on increasing hardness, total soluble solids, pH, vitamin C content, and decreasing total plate count (TPC) of fresh-cut melon stored at room temperature and refrigerated temperature. Applying 1% and 1.5% CMC in aloe vera gel edible coating could maintain the fresh-cut melon quality compared to other treatments at room temperature and refrigerated temperature, respectively